PENYERTAAN MANFAAT EKONOMI MAKRO BERUPA PDRB DALAM ANALISIS EKONOMI PEMBANGUNAN JALAN PENGHUBUNG BALI UTARA-SELATAN - Sudarsana, Dewa Ketut (Jurnal Ilmiah Teknik Sipil; Vol. 15, No. 2 Juli 2011)
Regional Economic growth of Bali province is not evenly distributed in each regency/city which could be due to the lack of connection and interaction between centre of economic activities. These conditions indicate the need of infrastructures and facilities that link the between two areas particulary road connecting North-South of Bali which has standards of capacity and accessibility. This paper analyses the economic aspects based on the existing economic developments using the cost-benefit analysis method. The economic benefits of road construction generally account for the direct benefit of road users in the form of savings on vehicle operating costs and the time value. Meanwhile, indirect benefit in the form of macroeconomic GRDP (Gross Regional Domestic Product) is included in this study. The study results are: (1). if the economic feasibility of a direct benefit on the interest rate of 12%, NPV = Rp 118.7 billion; BCR = 1.2 and IRR = 14.9%; (2) With the inclusion of GDP benefits of macro economic, the feasibility of this project is quite sensitive. This happened if the investment risk on the interest rate of 18%, 15% increase in costs and 15% decrease in benefit with the economic feasibility indicators NPV = Rp 146.09 billion; BCR = 1.24 and IRR = 18.9%.
Keywords: economic analysis, the direct benefits, indirect benefits, GDP